THE EFFECT OF NIFEDIPINE ON SURVIVE CELL, APOPTOTIC CELL AND NECROTIC CELL OF IPSILATERAL TESTICULAR GERMINAL EPITELIAL CELLS ON MALE WISTAR RATS WITH UNILATERAL TESTICULAR TORSION - Kurniawan, Andrie Rhomdhon; Hakim, Lukman; Soebadi, Doddy M (Indonesian Urological Association, 2019)
Objective: This study aimed to compare the number of survival, apoptotic and necrotic cells of ipsilateral testicular germinal epithelial cells in male wistar rats with unilateral testicular torsion between nifedipine given and control groups. Material & Methods: Thirty male wistar rats aged 10-12 weeks were randomly divided into 5 groups, each consisted of 6 rats. The negative control group (KN) underwent a sham procedure and left orchidectomy. Positive control group 4 (KP4) and 10 (KP10) performed left torsio testis 3 x 360 degrees medially for 4 hours and 10 hours respectively, then performed orchidectomy 4 hours after detorsion. The 4-hour (N4) and 10 hours (N10) nifedipine treatment group received the same treatment with positive control, but 30 min before detorsion performed, nifedipine were given intraperitoneal 100μg/kg. Within 1 hour after orchidectomy, cell count was calculated using flow cytometry. Results: It was found that the 4 (N4) and 10 hours (N10) nifedipine treatment group had a higher survival cells and also a lower number of apoptotic and necrotic cells compared to the positive control group. It was found that the 10 hours nifedipine treatment group (N10) had a lower number of apoptotic and necrotic cells compared to the 10 hour positive control group (KP10). The difference was statistically significant with p value <0.05. However, in KP4 and N4 group compared with KP10 and N10 group, higher apoptotic cells was obtained. This was a new phenomenon that needs to be investigated more deeply. Conclusion: Intraperitoneal administration of nifedipine prior to testicular detorsion may reduce the number of apoptotic and necrotic cells of testicular germinal epithelial cell, and may increase the number of survival cells in ipsilateral testes with unilateral testicular torsion.